Pengaruh Risiko terhadap Pertumbuhan Usaha Mikro, Kecil, dan Menengah (UMKM) - Aziz, Alfida; Pangestuti, Dewi Cahyani; Hidayati, Siti (Owner : Riset dan Jurnal Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy by supporting local economic growth and creating job opportunities. However, MSMEs are also confronted with various risks that can impact the sustainability of their businesses. This research aims to investigate and provide a comprehensive understanding of the influence of operational risk, interest rate risk, liquidity risk, and marketing risk on the growth of MSMEs in Daroyon, Cileles, Lebak, Banten. Given the background of MSMEs with limited capital and often facing business risks, this research emphasizes the importance of risk management to minimize losses. Most MSMEs in Daroyon engage in retail businesses, but they must compete with large stores and supermarkets, resulting in a decline in revenue. Despite the creative steps taken by small shop owners to retain customers, this risk highlights the need for adaptive and flexible risk management strategies. The study employs the Partial Least Square (PLS) method to analyze data. The findings reveal that operational risk, interest rate risk, liquidity risk, and marketing risk significantly influence the growth of MSMEs in Daroyon. These findings offer a profound understanding of the factors affecting MSMEs in Daroyon and can serve as a foundation for developing more effective risk mitigation strategies to support MSME growth in dynamic business conditions. The findings are also expected to serve as a foundation for stakeholders, the government, and local business practitioners to develop policies and risk management practices that are more adaptive and flexible.